Immunocorrection in Experimental Atopic Dermatitis Using Frozen-Dried Cord Blood Leukoconcentrate - Tarannik, Anna K.; Bondarovich, Nikolay A.; Gaevskaya, Yulia A.; Yampolskaya, Ekaterina Ye.; Grisha, Igor G.; Sokol, Larisa V.; Ostankov, Maksim V. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):173.